Pembacaan Tafsir Feminis Nasarudin Umar Sebagai Tranformasi Sosial Islam - Luthfi Maulana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
This paper will reveal a feminist interpretation as a reading that can transform Islamic social, because social understanding of society has long been eroded by the reading of classical interpretation, which tends to be biased and discriminative against women, so through reading the feminist interpretation of Nasarudin Umar, Opening a just horizon of reading (equality), peace for both men and women. Due to his tafsir exposure which tends to be more concerned with social conditions, Nasaruddin Umar tries to give a new color in interpreting the Qur'an with etymological analysis, hermeneutics and using history to examine many words in the Qur'an. So the pattern of interpreter is more to consider the macro-social aspects than the micro in each verse, in order to produce a reading of tafsir that can transform the social state of Islamic society.